Comprehensive Analysis of Clinical Significance, Immune Infiltration and Biological Role of m6A Regulators in Early-Stage Lung Adenocarcinoma - Zhou, Bolun; Gao, Shugeng (Frontiers in Immunology, 2021)
Recent publications have revealed that N6-methyladenosine (m6A) modification is critically involved in tumorigenesis and metastasis. However, the correlation of m6A modification and immune infiltration in early-stage lung adenocarcinoma (LUAD) is still uncertain. We performed NMF clustering based on 23 m6A regulators and identify three distinct m6A clusters and three m6A related genes clusters (m6A cluster-R) in early-stage LUAD. The immune infiltrating levels were calculated using CIBERSORT, MCPcounter and ssGSEA algorithms. And we established the m6A-predictive score to quantify m6A modified phenotypes and predict immunotherapeutic responses. We determined that tumor-related biological processes were enriched in m6A-C1 and pathways of cancer development and progression were enriched in m6A-C2. Based on the TME characteristics, different immune profiles were also identified among three m6A gene-related clusters. And the m6A-R-C2 was related to a favorable prognosis, whereas m6A-R-C3 had unfavorable clinical outcomes. The m6A-predictive score was built according to the expression levels of m6A-related genes, and patients could be stratified into subgroups with low/high scores. Patients with high scores had poor prognosis, enhanced immune infiltration, high tumor mutation burden and increased level of somatic mutation. Besides, patients with high scores had unfavorable clinical outcomes in the anti-PD-1 cohort, whereas the prognosis of high-score patients was better in the adoptive T cell therapy cohort. Our work highlights that m6A modification is closely related to immune infiltration in early-stage LUAD, which also contributes to the development of more effective immunotherapy strategies.